Histone acetyltransferase TaHAG1 interacts with TaPLATZ5 to activate TaPAD4 expression and positively contributes to powdery mildew resistance in wheat. Issue 2 (28th July 2022) - Song, Na; Lin, Jingchen; Liu, Xingbei; Liu, Zehui; Liu, Debiao; Chu, Wei; Li, Jinpeng; Chen, Yongming; Chang, Shumin; Yang, Qun; Liu, Xiaoyu; Guo, Weilong; et al.
Summary: Plants have evolved a two‐branched innate immune system to detect and cope with pathogen attack, which are initiated by cell‐surface and intracellular immune receptors leading to pattern‐triggered immunity (PTI) and effector‐triggered immunity (ETI), respectively. A core transducer including PAD4‐EDS1 node is proposed as the convergence point for a two‐tiered immune system in conferring pathogen immunity. However, the transcriptional regulatory mechanisms controlling expression of these key transducers remain largely unknown. Here, we identified histone acetyltransferase TaHAG1 as a positive regulator of powdery mildew resistance in wheat. TaHAG1 regulates expression of key transducer gene TaPAD4 and promotes SA and reactive oxygen species accumulation to accomplish resistance to Bgt infection. Moreover, overexpression and CRISPR‐mediated knockout of TaPAD4 validate its role in wheat powdery mildew resistance. Furthermore, TaHAG1 physically interacts with TaPLATZ5, a plant‐specific zinc‐binding protein. TaPLATZ5 directly binds to promoter of TaPAD4 and together with TaHAG1 to potentiate the expression of TaPAD4 by increasing the levels of H3 acetylation. Our study revealed a key transcription regulatory node in which TaHAG1 acts as an epigenetic modulator and interacts with TaPLATZ5 that confers powdery mildew resistance in wheat through activating a convergence point gene between PTI and ETI, which could be effective for genetic improvement of disease resistance in wheat and other crops.